Challenging assumptions around dementia : user-led research and untold stories /: user-led research and untold stories. (2023) - Ashworth, Rosalie; Fyvel, Sue; Hill, Alyson; Maddocks, Chris; Qureshi, Masood; Ross, David; Hay, Stuart; Robertson, Martin; Gilder, Willy; Henry, Winnie; Lamont, Myra; Houston, Agnes; et al.
No abstract available